COST DIFFERENCE OF ENHANCED RECOVERY AFTER SURGERY PATHWAY VS. CONVENTIONAL CARE IN ELECTIVE LAPAROSCOPIC CHOLECYSTECTOMY - Akhtar, Muhammad Shaheer; Khan, Nadim; Qayyum, Abdul; Khan, Said Zaman (Journal of Ayub Medical College Abbottabad, 2020)
Background: Enhanced recovery after surgery (ERAS) is a perioperative bundle aimed to reduce surgical stress. Significant reductions in length of hospital stay and associated costs have been reported in multiple studies in all surgical specialties. Purpose of the study was to compare the effect of Enhanced recovery protocols vs. conventional care on perioperative length of hospital stay and cost per patient in a government funded hospital. Methods: this randomized controlled trial was conducted in the department of General Surgery, unit B, Lady reading hospital, Peshawar from April to December 2018. One hundred and fifty patients were selected based on consecutive sampling. Random allocation into two groups of 75 (ERAS vs Conventional) was done based on computer generated numbers. Length of hospital stay and total direct costs were calculated. Frequency of Surgical site infections, readmissions and mortality was also recorded. Patient reported outcomes were recorded by Surgical Recovery Scale SRS. Results: Patients in the Enhanced recovery group showed a significant reduction in length of hospital stay 28.9 hours in ERAS group vs 40.5 hours in Conventional care group (p<0.001). Total per patient cost was reduced in the ERAS group PKR 6804 in comparison to the conventional care PKR 7682 (p<0.001). Patient reported outcomes measured on Surgical Recovery Scale SRS on discharge, day 3 of discharge and day 10 of discharge showed no significant difference between the two groups. Conclusion: Enhanced recovery protocols demonstrated a reduction in length of perioperative hospital stay and total cost despite similar post discharge recovery scores on Surgical Recovery Scale SRS and no increase in readmissions. Keywords: Minimally Invasive Surgery; Cholecystectomy; Laparoscopic; Hospital costs; Perioperative Care